2021
DOI: 10.21608/asejaiqjsae.2021.178864
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effects of Food Processing Byproducts on Neurological and Immunological Disorders of Obese Rats

Abstract: The present study aims to explore the effect of three byproducts that result from food processing processes, namely onion and bananas peels, and apricot seeds on neurological and immunological disorders of obese rats. Feeding of rats on diet induced obesity (DIO) leads to increase the BW than the control group. At the end of the experiment (8 weeks), rats of the normal group recorded 131.33% of baseline for the BW while obese group was 197.25% of baseline. Replacement of diets starch with banana peel powder (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…They can protect human body against damage by free radicals, which attack macromolecules including membrane lipids, proteins and DNA, lead to many health disorders/diseases including cancers, diabetes, heart vascular diseases, aging, inflammatory diseases, obesity, anemia, etc. [25,30,[107][108][109][110][111].…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…They can protect human body against damage by free radicals, which attack macromolecules including membrane lipids, proteins and DNA, lead to many health disorders/diseases including cancers, diabetes, heart vascular diseases, aging, inflammatory diseases, obesity, anemia, etc. [25,30,[107][108][109][110][111].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Generally, several previous studies indicated that that the level of MDA in the serum is a good marker of lipid peroxidation /oxidative stress, which is closely related to the pathogenesis of many diseases, including obesity [26,109,110,128,129,139]. It is one of the most important compounds in lipid peroxidation products and major product of the oxidation of polyunsaturated fatty acids, lipid hydroperoxides and conjugated dienes which found to be increased in plasma from obese subjects in many clinical studies [129,144].…”
Section: Effects Of Ssp On Biological Oxidants Levels Of Obese Ratsmentioning
confidence: 99%
“…A metabolic disease known as obesity is brought on by an excess of calories consumed and a lack of physical exercise [1]. Obesity is associated with several chronic circumstances, containing hypertension, dyslipidemia, and coronary heart ailments [2,3]. Body mass index (BMI), which is expressed as the weight in Kgs divided by the square of the height in meters (kg/m2), is a standard tool for determining the prevalence of bulky and obesity.…”
Section: Introductionmentioning
confidence: 99%